Keanekaragman Jenis Pakan Gajah Sumatera (Elephas Maximus Sumatrensis) Di Pusat Latihan Gajah Taman Nasional Way Kambas: Dietary Diversity of Sumatran Elephants (Elephas Maximus Sumatrensis) At Elephant Training Center Way Kambas National Park - Rawana Rawana; Agus Prijono; Evifani Alma Dian Elindawati (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2022)
The Sumatran elephant (Elephas maximus sumatrensis) is a rare animal that is threatened with extinction, so conservation is needed. Elephant Training Center (PLG) Way Kambas National Park is one form of in situ conservation. The availability of natural food is one of the factors that determine the success of conservation. The purpose of this study was to determine the composition and diversity of forest community species as elephant feeding habitats, and to determine the types of plants that elephants eat. Purposive sampling was used to collect data using nested plots, 1 x 1 m2 for seedlings and undergrowth, 5 x 5 m2 for saplings, 10 x 10 m2 for poles and 20 x 20 m2 for trees. The results showed that the vegetation making up the forest as a grazing habitat for Sumatran elephants consisted of 27 species belonging to 19 families. The vegetation that elephants eat is Symplocos thwaitesii, Imperata cylindrica, Colopogonium sp., Bridelia monoica, Vitex pinnata, Shorea sp., Pennisetum purpureum, Gluta renghas, Mimosa pudica, and Melastoma. The most widely available plant species belong to the Poaceae and Leguminoceae families. The diversity index of the seedling level of 2.49 was categorized as high, while the vegetation level of sapling, poles, and trees was categorized as low. Meanwhile, the evenness index at the seedling, sapling, pole and tree levels was categorized as high. The richness index for all levels of growth is categorized as moderate.